Nonkululeko Gobodo: a challenger challenged. Issue 3 (24th August 2022) - Ndaba, Zanele; Mitchell, Clare; Ngxola, Nomonde
Abstract : Learning outcomes: This case study aims to ensure that, students should be able to recognise the behaviours that influence the in-member out-member categorisation that transpires in the workplace, both from the leader's perspective and that of the followers; determine and understand the relevance of forming interpersonal relationships in the workplace and that interpersonal relationships create fundamentally positive or negative work experiences and impact on career opportunities in the workplace; gain an understanding of the internal bias and subjective comfort that leaders must actively overcome to establish an environment in which the entire team becomes in-group members; and be able to assess the contextual variables that contribute to the negative or positive aggravation of the leader–member exchange. Case overview/synopsis: It was 16 October 2014, and Nonkululeko Gobodo, Executive Chair of accounting firm SizweNtsalubaGobodo, was looking to her younger sister, Notemba Dlova, for emotional support, as she sought to address an important issue that was on the agenda of the firm's board of directors' meeting the following day. Tensions between her and Victor Sekese, Chief Executive Officer of the firm, were mounting, and a number of the directors were unhappy with the status quo. "How do you think I should address the issue?" she asked Dlova. Both sisters knew that at stake was Gobodo's future at the firm she had battled so hard to build up in the face of racial and gender stereotypes. Complexity academic level: The case study is appropriate for use in a range of postgraduate courses aimed at Master's in Management and Master of Business Administration (MBA)-level students. It is also suitable for use in postgraduate diplomas in business and executive education short courses. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 6: Human Resource Management.